Is your choice my choice? : the owners’ effect on pet dogs’ (Canis lupus familiaris) performance in a food choice task - E. Prato Previde; S.R. Marshall; P. Valsecchi (Animal Cognition, 2008)
This study investigates the influence of owners on their dogs’ performance in a food choice task using either different or equal quantities of food. Fifty-four pet dogs were tested in three different conditions. In Condition 1 we evaluated their ability to choose between a large and small amount of food (quantity discrimination task). In Condition 2 dogs were again presented with a choice between the large and small food quantity, but only after having witnessed their owner favouring the small quantity. In Condition 3 dogs were given a choice between two equally small quantities of food having witnessed their owner favouring either one or the other. A strong effect of the owner on the dogs’ performance was observed. In Condition 1 dogs as a group chose significantly more often the large food quantity, thus showing their ability to solve the quantity discrimination task. After observing their owner expressing a preference for the small food quantity they chose the large quantity of food significantly less than in the independent choice situation. The tendency to conform to the owner’s choice was higher when the dogs had to choose between equally small quantities of food (Condition 3) rather than between a large and a small one (Condition 2). These results provide evidence that dogs can be influenced by their owners even when their indications are clearly in contrast with direct perceptual information, thus leading dogs to ultimately make counterproductive choices.